OMAR MOHAMMAD ASY-SYAIBANI THOUGHT (RELIGIOUS-RATIONAL) THINKING ABOUT ISLAMIC EDUCATION - Wiliani; Maragustam Siregar (Jurnal Eduslamic, 2024)
This article explores the progressive style in Islamic education and the philosophy of education introduced by Omar Mohammad at-Toumy Ash-Shibani. The author uses a qualitative literature research method with the main source of the book Falsafatu at-Tarbiyah al-Islamiyah by Omar at-Toumy. The results of this article include concepts in the philosophy of Islamic education that accommodate the characteristics of progressivism, including balance, simplicity, and adaptation to the demands of the times. Omar Ash-Shibani emphasizes the importance of justice, equality, and a practical approach to teaching. The philosophy of Islamic education that is dynamic and based on religious values reflects Omar Ash-Shibani's great contribution to the development of Islamic education. In digging deeper into Omar Ash-Shibani's thoughts on Islamic education that combines religious and rational aspects, we use qualitative literature research methods. The main source used is the book Falsafatu at-Tarbiyah al-Islamiyah by Omar at-Toumy.